DEVIASI FONOLOGIS TUTURAN BAHASA INDONESIA ANAK - Yulianto, Bambang (Diksi, 2015)
This article explains the phonological deviations in Indonesian utterances of children with the age range from 1.0 to 2.6, which represents a stage of language development with the children of the age range from 1.0 to 1.6 producing their first single-word utterances (SWU), those of the age range from 1.6 to 2.0 producing their first word combinations (FWC), and those of the age range from 2.0 to 2.6 producing their first simple and complex sentences (SCS). The data show that 11 phonological deviation patterns are found in SWU, 13 phonological deviation patterns are found in FWC, and 7 phonological deviation patterns are found in SCS. On the basis of these available patterns, it could be stated that (1) the most productive patterns are stopping, gliding, nasalizing, and cluster reduction, (2) the deviation patterns tend to decrease as age increases, (3) as children get older, the reduplication pattern is abandoned and the deletion pattern decreases, and (4) a lateralization pattern occurs when children begin producing SCS. Most of the patterns are universal since they also occur in the utterances of subjects of other researchers. Keywords : patterns of phonological deviations, children utterances, underlying representation, phonetic representation, SWU, FWC, SCS